Evaluación de la bioestimulación de un consorcio microbiano para la degradación de PCB en suelo (2014)
ABSTRACT: In this work two microorganisms able to degrade polychlorinated biphenyl (PCB) were isolated from contaminated soil. The isolated microorganisms were identified as Pseudomonas spp. and Stenotrophomonas spp. In order to evaluate the efficiency of a bioaugmentation strategy for PCB contamination, PCB degrading microorganisms were inoculated into soil microcosms. PCB congeners 44, 66, 118, 138, 153, 170 and 180 were monitored during the bioremediation assay. In liquid culture using PCB as sole carbon source, removal percentages of 37%, 32,6%, and 15% were obtained for PCB 44, 66 and 118 respectively. Bioaugmentation assays were carried out using sterilized and non-sterilized soil, the highest removal percentages for all congeners were observed in sterilized soil, demonstrating the effect of native microorganism on the added inoculum. Key words: Bioremediation,PCB,biostimulation,biodegradation.